Cysticercosis: A preventable, but embarrassing neglected disease still prevalent in non–developed countries: We have the knowledge, we have the tools … but cysticercosis still affects humans and pigs in underdeveloped countries, and spreads to developed ones - Carpio Rodas, Luis Arturo (2015)
Taenia solium cysticercosis affects both humans and pigs. It has been considered an eradicable disease, and yet its prevalence remains stable in most endemic countries, due to the persistence of risk factors usually associated with the marginalization of an important sector of the population. In this chapter we will review key aspects of its epidemiology, clinical features, diagnosis, treatment, and prevention.